The utility of first trimester uterine artery Doppler, placental volume and PAPP-A levels alone and in combination to predict preeclampsia - Yücel, Burak; Gedikbaşı, Ali; Dündar, Öznur; Olgaç, Yusuf; Yıldırım, Do?ukan; Yıldırım, Gökhan Yetkin; Polat, İbrahim (Elsevier, 2016)
In this study, we aimed to evaluate the detection of pre-eclampsia (PE) by integrating uterine artery Doppler, placental volume, and pregnancy-associated plasma protein A (PAPP-A) levels in the first trimester. We prospectively recruited 602 women that underwent 11-13 weeks' aneuploidy screening. The mean pulsatility index (PI) of the uterine arteries and the placental volume were measured by ultrasonography. Measurement of PAPP-A levels has been performed at the same day' of ultrasonographic examinations. The 90th percentile of uterine artery PI and the 10th percentile of placental volume and PAPP-A levels were used as cut-offs. Uterine artery PI, placental volume, and PAPP-A levels had similar sensitivities in predicting PE (53.66%, 63.41%, and 70.73%, respectively). Use of the parameters in combination had better sensitivity. If one parameter was positive, the sensitivity was 92.68% with 85.20% specificity. If at least two parameters were positive, the sensitivity was 85.37% with 98.89% specificity. In conclusion, the combination of increased PI of uterine artery with low placental volume and low PAPP-A levels in the first trimester achieved better results than either test alone in the prediction of PE.
WOS: 000390825400006
PubMed ID: 27939466
Keywords: Pregnancy-Associated Plasma Protein A (PAPP-A); Placental Volume; Predict Preeclampsia